Les héritages paysagers de la viticulture dans le Val de Loire d’Orléans à Tours et ses abords périphériques - François Legouy (Projets de Paysage)
Landscaped inheritance of the viticulture in the Val de Loire, from Orléans to Tours and its periphery, beg the question of the definition of the Val de Loire, but also of the presence and the evolution of viticulture areas in this territory. The method consists in comparing a theorical landscaped model of the Val de Loire to the reality of the territory. Nevertheless, if this method has been proved by recent facts, it does not include long-term evolutions, as very well explained by Roger Dion. Older evolutions make us understand why vineyard has been maintained in such places, and not in others. By consequence, landscaped wine inheritances are sometimes tenuous, not much functional, and often have a decorative role. Indeed, Vineyard continues in unusual places and interstitial landscapes. It is more represented as a symbol which refers to a past Golden Age. For this theme, the landscape has without a doubt the same function than a palimpsest.